Patterning a Leaf by Establishing Polarities - Manuela, Darren; Xu, Mingli (Frontiers in Plant Science, 2020)
Leaves are the major organ for photosynthesis in most land plants and the leaf structure is optimized for maximum capture of sunlight and gas exchange. Three polarity axes, the adaxialabaxial axis, the proximodistal axis and the mediolateral axis are established during leaf development to give rise to a flattened lamina with a large area for photosynthesis and blades that are extended on petioles for maximum sunlight. Adaxial cells are small, tightly packed with many chloroplasts, and their fate is specified by HD-ZIP III transcription factors. Abaxial cells are large and loosely packed with many stoma, and their fate is established and maintained by YABBY family and KANADI family proteins. Establishment of the proximodistal axis involves the BTP-POZ domain proteins BLADE-ON-PETIOLE1 and 2, whereas homeobox genes PRESSED FLOWER and WUSCHEL-LIKE HOMEOBOX1 mediate the mediolateral axis. Here we summarize recent advances in leaf polarity establishment with a focus on the regulatory networks involved .